Do we need a European lender of last resort? - Uwe Vollmer (Intereconomics, 2009)
During a financial crisis, pressure on Central banks to act as a lender of last resort (LLR) and to offer emergency liquidity assistance to troubled banks increases. The European Central Bank, however, has announced that it does not regard it as its principal task to provide emergency liquidity to troubled banks and that it does not wish to disclose the conditions and practicalities of emergency liquidity assistance arrangements. In this paper, we investigate the benefits and the costs of centralising the LLR function in a monetary union and ask whether establishing an LLR in Europe could be useful.
Keywords: 330